A behavioral study of live captured coypu (Myocastor coypus) and raccoons (Procyon lotor) with respect to animal welfare - Schöttes, Franziska M.; Gethöffer, Friederike; Tost, Daniel; Kemper, Nicole; Siebert, Ursula (Frontiers in Veterinary Science, 2025)
Since 2016, coypu (Myocastor coypus) and raccoons (Procyon lotor) have been listed as invasive alien species (IAS) of European Union concern (The Implementing Regulation (EU) 1141/2016). The three-stage management plan stipulates the prevention of the further spread of species already established in Germany (Regulation (EU) 1143/2014 of the European Parliament and of the Council). Live trapping is a commonly used instrument to catch animals in hunting practice, but also in species conservation and pet protection. As part of a comprehensive study to improve animal welfare in live trapping, this paper focuses on a behavioral study with the aim of assessing the behavior of trapped animals in relation to stress. Video recordings were analyzed using a species adjusted ethogram and a quantitative observation method with focus on the animal in the trap over a maximum six-hour period. Blood and hair samples were taken for endocrinological examinations. The results showed large species-specific and individual differences in the expression of a wide range of behavior and coping strategies. As part of the stress assessment, it was concluded that external factors, among others the type of trap, have an influence on the behavior of coypu and raccoon. The raccoons showed different behaviors depending on the individual data. The endocrinological examinations of the stress parameters cortisol and dehydroepiandrosteron (DHEA) measured in serum and hair revealed differences between the species, indicating differing basal values. For coypu, the measurements indicated differences in serum and hair cortisol levels between juvenile and adult coypu. The study shows substantial indicators, such as the design of the trap type and the duration of capture, can be used to contribute to improve practices in live capture of (wild) animals.